Parents' Experiences of Receiving the Initial Positive Newborn Screening (NBS) Result for Cystic Fibrosis and Sickle Cell Disease. Issue 6 (20th April 2016) - Chudleigh, Jane; Buckingham, Sarah; Dignan, Jo; O'Driscoll, Sandra; Johnson, Kemi; Rees, David; Wyatt, Hilary; Metcalfe, Alison
Abstract: The clinical advantages of the newborn screening programme (NBS) in the UK are well described in the literature. However, there has been little exploration of the psychosocial impact on the family. This study followed the principles of grounded theory to explore parents' experiences of receiving the initial positive NBS result for their child with cystic fibrosis (CF) or sickle cell disease (SCD). Semi‐structured, qualitative interviews were conducted with 22 parents (12 mothers and 10 fathers) whose children had been diagnosed with CF or SCD via NBS and were under the age of 1 year at the time of interview. The main themes that arose from the data were; parents previous knowledge of the condition and the NBS programme, the method of delivery and parental reactions to the result, sharing the results with others, the impact on parental relationships and support strategies. Study conclusions indicate that most parents thought initial positive NBS results should be delivered by a health professional with condition specific knowledge, preferably with both parents present. Genetic counselling needs to include a focus on the impact of NBS results on parental relationships. Careful consideration needs to be given to strategies to support parents of babies who have positive NBS results both in terms of the psychological health and to assist them in sharing the diagnosis.